Atypiske lemmaer i Det Norske Akademis Store Ordbok - Noen betraktninger om deres plass og funksjon i en moderne diakron og deskriptiv ordbok - Lauvstad, Hanne (Nordiske Studier i Leksikografi, 2012)
Det Norske Akademis Store Ordbok (‘The Norwegian Academy’s Dictionary’), an extended and updated version of Norsk Riksmålsordbok (‘The Norwegian Riksmål Dictionary’, vols I–IV 1937–57, vols V–VI 1995) will be a descriptive, diachronic dictionary covering the Norwegian Bokmål and Riksmål, and, as such, one of two national dictionaries for the Norwegian language. As modern Bokmål has its origins in both Old Norse and Danish, the dictionary’s vocabulary poses certain challenges to lemmatization. The dictionary contains several archaisms and dialect words, i.e. diachronic and diatopic variants, among them several atypical lemmas, which have to be adapted and standardized as part of the dictionary’s macrostructure. Examples illustrate how this problem may be solved in the light of the basic criteria for the lemmatization: etymology, part of speech, gender and inflection, style nuance and usus.